2015
DOI: 10.1590/1516-1439.311514
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Fibers from Pineapple's Crown, Rice Husks and Cotton Textile Residues

Abstract: Fibers from pineapple's crown (PCF), rice husks (RH) and cotton textile residues (RTF) were characterized by SEM, X-ray diffraction, FTIR and thermogravimetric analysis. Moisture content, water absorption, density and the distribution of the diameter of the fibers were also evaluated. RTF showed cylindrical microstructure with smooth surface, PCF showed cellular structure and the microstructure of RH is globular, showing cell pattern of the outer surface epidermis which is well organized and has a corrugate st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
6
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(10 citation statements)
references
References 39 publications
2
6
0
2
Order By: Relevance
“…Also, elongated acicular structures are observed, which resemble "hairs", typical of the fibrous structure of certain cereals. Other authors [20,30,31] also observed this morphology. In Fig.…”
Section: Characterization Of Raw Materialssupporting
confidence: 59%
“…Also, elongated acicular structures are observed, which resemble "hairs", typical of the fibrous structure of certain cereals. Other authors [20,30,31] also observed this morphology. In Fig.…”
Section: Characterization Of Raw Materialssupporting
confidence: 59%
“…Weight loss temperature ranged at about 250-420°C, indicating the degradation of cellulose. The cellulose degradation temperature of other lignocellulosic fibres like sugarcane was 350°C (Hoi & Martincigh, 2013), amazon piassava (361°C) (Rebelo et al, 2019), pineapple's crown, rice husks and cotton (257-390°C) (Prado & Spinacé, 2015). From this figure, it can be observed that the pristine LeLeF started to decompose at 286 °C while for 6, 8 and 10 wt% NaOH treated LeLeF, they started to decompose at 287°C, 291°C, and 293°C respectively.…”
Section: Natural Fibrementioning
confidence: 99%
“…The hemicellulose content of cotton linters (which is negligible) was also used as the hemicellulose content of the jeans cotton, since it was expected that the presence of dye and other additives in the jeans cotton would give misleading results. This is a reasonable assumption as textile-grade cotton contains negligible hemicellulose (Prado and Spinacé 2015).…”
Section: Hemicellulose Contentmentioning
confidence: 99%